PENGARUH LATIHAN DRIBBLE DENGAN POLA SLALOM TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PERMAINAN BOLA BASKET PUTRA TIM SMK MUHAMMADYAH 1 PEKANBARU - Rina Sri Yunita; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is the dribbling skills on the men's team SMK Muhammadyah 1 Pekanbaru is still not good, this is seen when the men's team herded, looks stiff and most of the way herded the ball is still a lot of being pounded and eyes still fixed on the ball. The type of this research is experimental (experimental) research, with O1  X O2 research design and using preetest-posttest design one-group research design. Population in this research is basketball team of SMK Muhammadyah 1 Pekanbaru which amount 10 people. The sample technique used is total sampling (saturated samples), where all the population is sampled. Thus the sample in this study amounted to 10 athletes SMK Muhammadyah 1 Pekanbaru. The data retrieval technique can be from pre-test and post-test. The instrument performed in this studied is the dribbling test, which aims to measure the dribbling ability. The variables that exist in this research is dribble exercise with slalom pattern which is denoted by X as independent variable, while dribbling ability is denoted by Y as dependent variable. After that, the data were processed with statistics, to test the normality by liliefors test with a significant level of 0.05. The hypothesis that is proposed is the effect of dribble exercise with slalom pattern of dribbling skills on the basketball game of men's team SMK Muhammadyah 1 Pekanbaru. Based on the analysis of T test then obtained the conclusion that is: Tcount of 7.18 and Ttabel 1.833, means Tcount> T table. It can be concluded that Ho is rejected and HI accepted, it concludes that there is a significant effect of dribble training with slalom pattern on bolting skills.Keywords : Dribble Slalom, Dribbling skills